Economics and the public purpose - Galbraith, John Kenneth (London : Deutsch, 1973)
This book seeks to bring the market sector of the economy and therewith the whole economic system into focus.
Includes bibliographical references and index.
rpm 13/06/2017
Loans
Keywords: Corporations; Corporations--United States; Industrial policy; Industrial policy--United States; United States--Economic conditions--1971-1981.; United States--Economic policy--1971-1981.; Economics $1 (BTheoriess; Comparative economics; Market Economy; United States; United States